PD-1/PD-L1 checkpoint inhibitors in advanced hepatocellular carcinoma immunotherapy - Li, Qian; Han, Jingjing; Yang, Yonglin; Chen, Yu (Frontiers in Immunology, 2022)
Hepatocellular carcinoma (HCC) has a high prevalence and mortality rate worldwide. Sorafenib monotherapy has been the standard of first-line treatment for advanced HCC for a long time, but there are still many shortcomings. In recent years, with the deepening of research on tumor immune microenvironment, researchers have begun to explore new approaches in immunotherapy, and the introduction of immune checkpoint inhibitors has brought fundamental changes to the treatment of HCC. Programmed cell death protein 1 (PD-1) is an immune checkpoint molecule that plays an important role in down-regulating immune system function and promoting tolerance. Programmed cell death ligand 1 (PDL-1) is involved in tumor immune evasion by binding to PD-1, resulting in failure of treatment. Currently, immunotherapy targeting the PD-1/PD-L1 axis has achieved unprecedented success in HCC, but it also faces great challenges, with its low remission rate still to be solved. For most patients with HCC, the PD-1/PD-L1 pathway is not the only rate limiting factor of antitumor immunity, and blocking only the PD-1/PD-L1 axis is not enough to stimulate an effective antitumor immune response; thus, combination therapy may be a better option. In this study, changes in the immune microenvironment of HCC patients were reviewed to clarify the feasibility of anti-PD-1/PD-L1 therapy, and a series of monotherapy and combination therapy clinical trials were summarized to verify the safety and efficacy of this newly developed treatment in patients with advanced HCC. Furthermore, we focused on hyperprogressive disease and drug resistance to gain a better understanding of PD-1/PD-L1 blockade as a promising treatment.